Technical Note: The Effect of The Fed’s Quantitative Easing Policy on the Performance of Listed Companies and the Banking Sector in Indonesia - Yanuar Rizky (Australasian Accounting, Business and Finance Journal, 2015)
While the efficient market hypothesis suggests that stock price reflects the fundamental condition of companies, which could affect investors’ decisions, this technical note reports empirical evidence that stock price is also influenced by the public’s perception of the market situation. This note shows that the source of funds circulating in the Indonesia Stock Exchange is related to excess liquidity resulting from the policy of quantitative easing (QE) by developed countries’ central banks. Banks funding assets with debt results in leverage relationships with the Capital Adequacy Ratio (CAR) negatively affected. Thus it is evident that the Indonesian banking strategy is "reactive" and is influenced by external factors. External factors can be influenced by global issues as well as internal (enterprise performance) issues. Therefore foreign and global issues may be important (perhaps dominant) in determining the perceptions of the Indonesian stock market.
Keywords: Indonesian stock exchange; bank; quantitative easing